Examining the value of money in turkey over the long term (1469-2009) - Abdullah, Adam (Canadian Center of Science and Education, 2013)

(untitled)
This paper aims to examine the tremendous loss of value of money over the long term during the Ottoman Empire and the Republic of Turkey between 1469-2009. By 1844, 1.1 Ottoman lira exchanged for one English pound, but in 2005, 1.5 million Turkish lira exchanged for one U.S. dollar. By critically examining the value and purchasing power of money in Ottoman-Turkey, this paper compares empirical evidence and statistics through long term analysis of silver and commodity price indices, as to which medium of exchange provides for the best store of value. This paper discovers that monetary policy should not target stable prices, by managing the quantity or purchasing power of money, but instead adopt a monetary theory of value involving a stable currency, free of monetary management, permitting a stable purchasing power and thus stable prices.